CRITICISM ON THE PHILOSOPHICAL METHOD OF IBN TAYMIYYA, AND HIS REASONS FOR THE TAKFIR OF ISLAMIC PHILOSOPHERS - Muzaffer BARLAK (Fırat University, 2020)
It is possible to evaluate Ibn Taymiyya’s approach to Islamic philosophers and philosophy in two ways. The first one is the critical attitude towards philosophical method, and the second one is the refusal to the solutions offered by philosophers on theological issues. It is seen that Ibn Taymiyya’s criticism of the philosophical method is collected in three points. The first one is the status given to the mind in the face of narration, the second one is the necessity for the interpretation regarding the Verses of the Quran and Hadiths (i.e. the nas), the third is that the science of logic was identified as the only method to reach accuracy in any subject. Ibn Taymiyya claims that Islamic philosophers produce thoughts on an invalid basis that is not based on the basis of knowledge because of their attitudes on these issues; and therefore, they cannot stay away from making mistakes. It is seen that the issues, which are the subject of the rejection of Ibn Taymiyya, were collected under eight items regarding the opinions that Islamic philosophers put forward on theological issues. These eight articles include the seniority of the universe, the fact that Allah does not know the particulars (i.e. the cuz), the fact that the “mead” “resurrection” (i.e. the recreation of the bodies of people in the Hereafter) will not take place, prophecy, the angels, the word of Allah, the intercession, the denial of Allah’s “mashiat” (i.e. the freedom of Allah in His actions) and his mightiness. Ibn Taymiyya detailed the opinions of Islamic Philosophers on these eight issues, and expressed his criticism on each issue. In addition, he also added that Islamic philosophers became disbelievers because of their opinions on these issues. The purpose of this article was to address and examine ibn Taymiyya’s three critiques on the philosophical method, and his eight rejections on theological issues that led to him to criticize Islamic philosophers.